European service-learning experiences in higher education and the Freirean concept of seminar (Escola Superior de Educação de Paula Frassinetti, 2022)
Service-learning is growing gradually in European higher education. It aims to instil a sense of civic engagement and responsibility in students and work towards positive social change within society while developing curricular competencies. For some advocates, Paulo Freire's workings would serve as a theoretical anchor for service-learning since he imagined education as fostering a critical and active citizenry. This paper addresses the influence his writings have had on European practitioners. Qualitative data collected by the EOSLHE has been analysed and a content analysis was made of the descriptive summaries of 144 experiences. The Freirean notion of seminar applied to service-learning systematises popular wisdom and contributes to a new sense of evolving the social identities of the students toward a fairer society.